PENINGKATAN KEMAMPUAN PEDAGOGIK GURU MELALUI REVITALISASI KEARIFAN LOKAL BUGIS DALAM PEMBELAJARAN DI SMP NEGERI 1 GOWA - Dian Dwi Putri Ulan Sari Patongai; Oslan Jumadi; Andi Asmawati Azis; Arifah Novia Arifin; Oriny Tri Ananda; Arsad Bahri; Nurul Magfirah Rahman (Universitas Negeri Makassar, 2026)
This Community Service Program (PKM) aimed to improve teachers’ pedagogical competence through the revitalization of Bugis local wisdom in Biology learning at SMP Negeri 1 Gowa. The main problem faced by the partner school was the limited ability of teachers to implement innovative, contextual, and culture-integrated learning approaches. In addition, the integration of Bugis local wisdom values into classroom learning was still minimal. The methods applied in this program included socialization, training, material presentation, and mentoring in developing local wisdom-based learning tools. The program was conducted on August 28, 2025, involving 15 teachers. Evaluation was carried out through participant satisfaction questionnaires as well as pretests and posttests to measure teachers’ understanding improvement. The results showed that teachers were able to develop teaching modules and student worksheets integrated with Bugis local wisdom values such as siri’ na pacce, mappasituju, and environmental wisdom practices within Biology learning. The average participant score increased significantly from 64.5 in the pretest to 96.2 in the posttest. Participant satisfaction was also categorized as very satisfactory, with an average score of 4.56. Therefore, this PKM activity successfully enhanced teachers’ pedagogical competence and encouraged the creation of more contextual, innovative, and meaningful Biology learning through the integration of Bugis local wisdom. Keywords: pedagogical competence, Bugis local wisdom, Biology learning, cultural revitalization, community service program